Bahasa Inggris: A Visual Analysis - Aulia Azahro , Fany; Abdul Rosyid, Ocid; Kasamira Dewi Abrori, Rafila; Puspitasari, Dewi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Children’s animated films play an important role in shaping children’s perceptions of social and cultural values, including tolerance and religious moderation. This study aimed to understand how messages about religious tolerance and moderation are communicated through symbols, scenes, and character interactions in the Upin & Ipin series. This study used a qualitative approach with a visual discourse analysis method to examine the visual representation in the series. The data analysis technique involved observing scenes that show interreligious interactions, religious celebrations, and respectful behavior between characters with different cultural and religious backgrounds. Each scene was analyzed based on the visual and narrative context to identify messages of religious moderation. Data were analyzed using descriptive coding and thematic analysis to find patterns of visual depictions of religious moderation. The results showed that Upin & Ipin series consistently displays the values ​​of religious moderation through harmonious characters in participating in religious celebrations. This visual message emphasizes the importance of mutual respect in a multicultural society. This study implies that children’s media, especially cartoon film, can be used to teach the values ​​of religious moderation and tolerance from an early age.